Electro-Acupuncture Regulates Metabolic Disorders of the Liver and Kidney in Premature Ovarian Failure Mice - Chen, Min; He, Qi-da; Guo, Jing-jing; Wu, Qi-biao; Zhang, Qi; Yau, Yuen-ming; Xie, Yu-feng; Guo, Zi-yi; Tong, Zi-yan; Yang, Zong-bao; Xiao, Lu (Frontiers in Endocrinology, 2022)
As per the theory of traditional Chinese medicine (TCM), the liver and kidney dysfunction are important pathogenies for premature ovarian failure (POF). POF is a common gynecological disease that reduced the pregnancy rate. Electro-acupuncture (EA) is a useful non-pharmaceutical therapy that supposedly regulates the function of the liver and kidney in the treatment of POF with TCM. However, the underlying mechanism of EA in the treatment of POF has not been adequately studied through metabonomics with reference to the theory of TCM. Accordingly, we investigated the effect of EA on the liver and kidney metabolites in POF mice through metabolomics. POF mice were established via intraperitoneal injection of cisplatin. Both Sanyinjiao (SP6) and Guanyuan (CV4) were stimulated by EA for 3 weeks. The biological samples (including the serum and the ovary, liver, and kidney tissues) were evaluated by histopathology, molecular biology, and 1HNMR-based metabolomics to assess the efficacy of EA. 1HNMR data were analyzed by the Orthogonal Partial Least Squares Discrimination Analysis (OPLS-DA). The results revealed that EA was beneficial to ovarian function and the menstrual cycle of POF. Both the energy metabolism and neurotransmitter metabolism in the liver and kidney were regulated by EA. Notably, EA played an important role in regulating energy-related metabolism in the kidney, and the better effect of neurotransmitter-related metabolism in the liver was regulated by EA. These findings indicated that the ovarian functions could be improved and the metabolic disorder of the liver and kidney caused by POF could be regulated by EA. Our study results thus suggested that the EA therapy, based on the results for the liver and kidney, were related to POF in TCM, as preliminarily confirmed through metabolomics.